A Pro-Market Agenda for El Salvador - Eduardo Engel (Yale University, Economic Growth Center, 2005)
This paper argues that, despite important productivity gains, reforms have benefited consumers much less than expected in El Salvador. Antitrust legislation, consumer protection and an adequate regulation of privatized utilities are central ingredients of a successful market economy. Major reforms that are needed in each one of these areas in El Salvador are described.
Keywords: D18; L40; L51; L94; L96; O12; 330; Market reform; Antitrust legislation; Consumer protection; Privatization; Regulation of utilities; Regulierung; Versorgungswirtschaft; Kartellrecht; Verbraucherschutz; Privatisierung; El Salvador